Upregulation of Long Non-Coding RNA GCC2-AS1 Facilitates Malignant Phenotypes and Correlated With Unfavorable Prognosis for Lung Adenocarcinoma - Yu, Fengqiang; Liang, Mingqiang; Wu, Weidong; Huang, Yu; Zheng, Jiantao; Zheng, Bin; Chen, Chun (Frontiers in Oncology, 2021)
Background: The role of long noncoding RNA GCC2-AS1 in all types of primary malignant tumors is poorly understood. In this study, we investigated the expression levels, prognostic value and biological effects of GCC2-AS1 in lung adenocarcinoma (LUAD). Methods: We used data obtained from our samples and the TCGA database to examine the expression of GCC2-AS1 and its prognostic value for LUAD patients. Functional experiments were conducted to investigate the effect of GCC2-AS1 on LUAD cells. Genes that were differentially expressed in GCC2-AS1-low and -high groups were analyzed by an enrichment analysis. Additionally, a nomogram model was created and subgroup analyses were performed to further determine the prognostic value of GCC2-AS1 in LUAD. Results: GCC2-AS1 was significantly upregulated in lung adenocarcinoma tissues as compared with normal tissues. Depletion of GCC2-AS1 levels inhibited the proliferation and invasion of LUAD cells in vitro. Elevated levels of GCC2-AS1 remarkably correlated with an unfavorable overall survival time and were identified as an independent prognostic marker for LUAD patients. Enrichment analyses conducted using the GO, KEGG, and GSEA databases were performed to identify biological pathways that might involve GCC2-AS1. Several subgroups were found to have a significant prognostic value for GCC2-AS1-low and -high groups. Conclusions: Our findings suggest that GCC2-AS1 can serve as a promising prognostic biomarker for LUAD patients.